Efficacy of high-intensity, low-volume interval training compared to continuous aerobic training on insulin resistance, skeletal muscle structure and function in adults with metabolic syndrome: study protocol for a randomized controlled clinical trial (Intraining-MET) (2018)
ABSTRACT: Evidence of the efficacy of high-intensity, low-volume interval training (HIIT-low volume) in treating insulin resistance (IR) in patients with metabolic disorders is contradictory. In addition, it is unknown whether this effect is mediated through muscle endocrine function, which in turn depends on muscle mass and fiber type composition. Our aims were to assess the efficacy of HIIT-low volume compared to continuous aerobic exercise (CAE) in treating IR in adults with metabolic syndrome (MS) and to establish whether musclin, apelin, muscle mass and muscle composition are mediators of the effect. Methods: This is a controlled, randomized, clinical trial using the minimization method, with blinding of those who will evaluate the outcomes and two parallel groups for the purpose of showing superiority. Sixty patients with MS and IR with ages between 40 and 60 years will be included. A clinical evaluation will be carried out, along with laboratory tests to evaluate IR (homeostatic model assessment (HOMA)), muscle endocrine function (serum levels of musclin and apelin), thigh muscle mass (by dual energy x-ray absorptiometry (DXA) and thigh muscle composition (by carnosine measurement with proton magnetic resonance spectroscopy (H–MRS)), before and after 12 weeks of a treadmill exercise program three times a week. Participants assigned to the intervention (n = 30) will receive HIIT-low volume in 22-min sessions that will include six intervals at a load of 90% of maximum oxygen consumption (VO2 max) for 1 min followed by 2 min at 50% of VO2 max. The control group (n = 30) will receive CAE at an intensity of 60% of VO2 max for 36 min. A theoretical model based on structural equations will be proposed to estimate the total, direct and indirect effects of training on IR and the proportion explained by the mediators. Discussion: Compared with CAE, HIIT-low volume can be effective and efficient at improving physical capacity and decreasing cardiovascular risk factors, such as IR, in patients with metabolic disorders. Studies that evaluate mediating variables of the effect of HIIT-low volume on IR, such as endocrine function and skeletal muscle structure, are necessary to understand the role of skeletal muscle in the pathophysiology of MS and their regulation by exercise. Trial registration: NCT03087721. High-intensity Interval, Low Volume Training in Metabolic Syndrome (Intraining-MET). Registered on 22 March 2017, retrospectively registered.